STRATEGI PENGEMBANGAN KOPERASI LEMBAGA KEUANGAN MIKRO AGRIBISNIS (LKM-A) GAPOKTAN SARI MAKMUR KECAMATAN METRO TIMUR KOTA METRO - Aurora Afifah Yasmin; Dyah Aring Hepiana Lestari; Muhammad Irfan Affandi (Lampung University, 2019)
This research aims to analyze the internal and external environment, arrange development strategies, and determine priority strategies of Microfinance Institutions Farmer Groups Sari Makmur Cooperative. This research isperforms a case study method. Respondents were 13 people consist of organizers and members of the cooperative, expert, and regulator. Data analysis method used in this research was qualitative analysis method. The results showed that the main internal strengths of the cooperative were its legal status and registered status at the financial services authority. The main weakness was the lack of awareness of members in the cooperative. Externally, cooperative faced major opportunity in the form of the need for easy and fast loan services and the main threat of increasing community living costs. The priority strategies that could be used in the development and sustainability of the cooperative microfinance were using accounting software for financial data processing to improve cooperative’s financial management, improving the quality of cooperative’s organizer and managers by providing internal training and engaging in external training conducted by the government or other institutions, and improving the excellent service to meet the needs of cooperative’s members.Key words: cooperative, microfinance, strategies